OPTIMASI PARAMETER MESIN ULTRASONIC WELDING UNTUK PENYAMBUNGAN MATERIAL TERMOPLASTIK - Dodi Mulyadi; Sukarman Sukarman; Amir Amir; Bella Sofiyanti; Azis Adhi Nugroho (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2024)
Ultrasonic welding is the joining of materials using of heat generated from high frequency mechanical movements. Known as an efficient process in many applications, such as in textile, packaging and automotive industries. One of the materials that can be joined using ultrasonic welding is thermoplastic material because there is no polymer degradation found in the product after the welding process. In most practices, parameters determining for ultrasonic welding machines uses a trial and error method, several parameters are determined to vary, such as welding pressure, welding time, holding time, drop speed and trigger pressure. To determine the correct variation of values, the Taguchi method is the right choice, determining the variable matrix is ​​very easy, commonly used, and many studies have proven that the Taguchi method is reliable. In this research, the product to be studied is a medical device, which uses thermoplastic polymer as its material. This research has produced the best variable variation of ultrasonic welding machine parameters: welding pressure of 20.00 psi; welding time of 0.21 seconds; holding time of 0.16 seconds; horn descent speed of 3.00 seconds; and trigger pressure of 4.00 psi. The defective products on appearance had reduced to 0.07% from the previous 1.08%.